KAJIAN SOSIAL EKONOMI MASYARAKAT BERBASIS GENDER DALAM KONTEKS ADAPTASI PERUBAHAN IKLIM DI KABUPATEN SUMBAWA - Baiq Yulfia E. Yanuartati; Muhammad Nursan; Aliefman Hakim; Fadli Fadli; Arya Ningsih; Nilla Pradita (Departmen of Agribusiness, Economics and Management Faculty, Bogor Agricultural University, 2026)
Climate change in Sumbawa Regency has significant impacts on local ecosystems and communities, particularly through rising temperatures, shifting rainfall patterns, droughts, and increased disaster risk. These conditions affect key livelihood sectors such as agriculture, livestock, and water resources, thereby weakening household food security and economic resilience. This study aims to analyze community livelihoods from a gender perspective within the context of climate change adaptation, focusing on access, participation, control, and the benefits of resources. This research employed a descriptive qualitative approach through surveys, in-depth interviews, and field observations in Kerekeh Village over a three-month period. Findings reveal that limited education, low-income levels, and dependence on primary sectors are the forms of household vulnerability. Patriarchal norms continue to shape household structures, with men often acting as primary decision-makers, while women’s roles in agricultural production and economic decision-making remain limited. However, a shift toward more collective household labor is emerging, especially through women’s involvement in livestock activities and their roles as heads of households. The analysis of natural, physical, social, and financial resources highlights gender-based disparities, with men dominating access to productive assets and employment-related information. Community awareness of climate change impacts is relatively high, especially concerning extreme weather and drought. Adaptation strategies include income diversification, savings utilization, and engagement in informal work, with gender influencing the choice and priority of these strategies. This study recommends strengthening community capacity, especially for women through education, digital literacy, accessible climate information, improved access to land and capital, and the development of gender-inclusive community-based groups to support sustainable livelihoods under climate stress.